2016
DOI: 10.1212/nxg.0000000000000087
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis risk loci and disease severity in 7,125 individuals from 10 studies

Abstract: Objective:We investigated the association between 52 risk variants identified through genome-wide association studies and disease severity in multiple sclerosis (MS).Methods:Ten unique MS case data sets were analyzed. The Multiple Sclerosis Severity Score (MSSS) was calculated using the Expanded Disability Status Scale at study entry and disease duration. MSSS was considered as a continuous variable and as 2 dichotomous variables (median and extreme ends; MSSS of ≤5 vs >5 and MSSS of <2.5 vs ≥7.5, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 41 publications
0
58
1
1
Order By: Relevance
“…On the other hand, our results are in disagreement with the only other study performed in Slavs which showed no individual association between rs1800693 and MS in the Russian population (Bashinskaya et al, 2015). Further analyses in subgroups stratified by sex or presence of the major MS risk allele consistent with most other studies performed in patients of predominantly European origin (Baranzini et al, 2009;Brynedal et al, 2010;Comabella et al, 2013;George et al, 2016;IMSGC et al, 2013IMSGC et al, , 2011IMSGC, 2011a;Lin et al, 2014;Ottoboni et al, 2013;Pan et al, 2016). However, possible effect of rs1800693 on disease course cannot be fully excluded yet, as suggested by a recent study in Russians which reported an association of C allele with moderate-to-severe MS (MSSS > 3) and unfavourable variants of MS manifestation, such as motor disorders, brainstem disorders, impaired coordination, pelvic disorders, mental disorders or polysymptomatic onset (Kulakova et al, 2016).…”
Section: Discussioncontrasting
confidence: 97%
“…On the other hand, our results are in disagreement with the only other study performed in Slavs which showed no individual association between rs1800693 and MS in the Russian population (Bashinskaya et al, 2015). Further analyses in subgroups stratified by sex or presence of the major MS risk allele consistent with most other studies performed in patients of predominantly European origin (Baranzini et al, 2009;Brynedal et al, 2010;Comabella et al, 2013;George et al, 2016;IMSGC et al, 2013IMSGC et al, , 2011IMSGC, 2011a;Lin et al, 2014;Ottoboni et al, 2013;Pan et al, 2016). However, possible effect of rs1800693 on disease course cannot be fully excluded yet, as suggested by a recent study in Russians which reported an association of C allele with moderate-to-severe MS (MSSS > 3) and unfavourable variants of MS manifestation, such as motor disorders, brainstem disorders, impaired coordination, pelvic disorders, mental disorders or polysymptomatic onset (Kulakova et al, 2016).…”
Section: Discussioncontrasting
confidence: 97%
“…This clinical course is unpredictable, and no tools for prognosis currently exist. Several studies have explored the genetic basis of clinical course, age of onset and severity, although no genome‐wide significant associations have been discovered 36, 37, 43, 74, 75, 76, 77. Whether more detailed disease parameters are more prone to error measurement, systematic differences across centres or simply not heritable remains to be determined, but a recent study showing that clinical scores can be predictive across centres suggests that lack of heritability is not the issue 78…”
Section: Future Directionsmentioning
confidence: 99%
“…The rs7665090 risk variant is not known to increase MS severity or likelihood of disease progression. Indeed, GWAS of disease severity have to date not yielded candidates at genome-wide significance 26 and a recent study found that genetic risk variants for MS susceptibility do not influence disease severity 27 , suggesting that rs7665090 risk variantmediated lymphocyte recruitment does not drive MS severity. Our data show a moderate association between risk variant and increased white matter lesion load in MS patients; however, although counterintuitive, T2 lesion volume does not correlate with disability as measured by EDSS and is not a surrogate marker for disease severity 24,28 .…”
Section: Discussionmentioning
confidence: 99%